Decrease of Epstein-Barr Virus Anti Early Antigen Imunoglobulin a Levels and Primary Tumor Size in PostCisplatin-Paclitaxel Chemotherapy in Nasopharyngeal Carcinoma Patients - Elvi Syahrina Fiorisa1, Achmad Chusnu Rhomdhoni1, Budi Sutikno1, Anggraini Dwi Sensusiati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nasopharyngeal carcinoma (NPC) associated with Epstein-Barr virus (EBV) chronic infection is a common head and neck malignancy in South China and Indonesia. Although radiation and chemotheraphy is the main theraphy, it requires repeated and invasive biopsy for pathological evaluation. Therefore, a marker is required for screening including the level of anti early antigen imunoglobin a serology level. Method: Pre-pots test, longitudinal cohort design. The PTV of 18 samples were examined using CT scan, while their serum EBV anti EA IgA level were examined using pre and post three series-cisplatin-paclitaxel chemotherapy ELISA. Results: Although there was no significant changes in the level of anti EA IgA, however we found a decrease in the mean of pre-chemotherapy anti EA IgA level from 136.49 U/ml to 124.61 U/ml. There was significant changes in the VTP in pre and post-chemotherapy (p<0.05). The mean of VTP in pre-chemotherapy was 66.26 cm3 (SD-38.61 cm3), while in post-chemotherapy was 31.64 cm3 (SD-27.5 cm3). The delta mean of changes in anti EA IgA level was 11.8 U/ml and in VTP was 34.62 cm3. No correlation was found between the changes of anti EA IgA and the changes of VTP in post-chemotheraphy (p>0.05). However, decreases were found in the level of EBV EA IgA and PTV in pre and post NPC patients. Conclusion: There were decreases of serum EBV EA IgA level and PTV in pre and post-chemotherapy NPC patients.